PIAGAM JAKARTA DAN HUBUNGANNYA DENGAN PERDA-PERDA BERNUANSA SYARI’AH - Deni Syaputra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In the midst of the hustle and bustle of the dynamics of openness in this reform era, various Islamic groups have again voiced the Islamic Sharia as an agenda that should receive attention. demands that carry the Islamic Shari'ah have also reached the effort to positify the Shari'a into national legislation both at central and regional levels. The government has also prepared a Bill on the Law of Applied Religious Courts. This bill is an attempt to transform the rules of Islamic law, as a law that lives in society into positive law. Its scope is the legal fields which are the authority of the Religious Courts. The drum of regional autonomy is the main entry point for the emergence of all local regulations as a manifestation of the regulations which both are attributive (inherent) and delegative (derived).